2016
DOI: 10.1038/srep32763
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of laser-driven electron-multirescattering dynamics in high-order harmonic generation

Abstract: Multiple rescattering processes play an important role in high-order harmonic generation (HHG) in an intense laser field. However, the underlying multi-rescattering dynamics are still largely unexplored. Here we investigate the dynamical origin of multiple rescattering processes in HHG associated with the odd and even number of returning times of the electron to the parent ion. We perform fully ab initio quantum calculations and extend the empirical mode decomposition method to extract the individual multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The present study is devoted to a description of tunneling ionization employing Bohmian Mechanics [11][12][13], which has recently attracted much attention [14][15][16][17][18][19][20][21][22][23][24]. It will be shown that computing the streamlines of the wavefunction probability over time provides valuable insights and a natural route to understanding complex ultrafast mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The present study is devoted to a description of tunneling ionization employing Bohmian Mechanics [11][12][13], which has recently attracted much attention [14][15][16][17][18][19][20][21][22][23][24]. It will be shown that computing the streamlines of the wavefunction probability over time provides valuable insights and a natural route to understanding complex ultrafast mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…6,11,12 For long laser wavelengths, the HOR can have stronger manifestations in the HHG. 11,[13][14][15][16][17][18][19][20][21] Especially in ref. 6 for helium atom, it is proposed that targets illuminated by few-cycle mid-infrared laser pulses can generate zeptosecond pulses due to the interference between the first-and third-order return trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the difference between the two proposals (interference vs. reducing HOR schemes), they are examples of electron trajectory manipulation, the method is known before to generate attosecond pulse trains (APT). [22][23][24][25][26] As mentioned above, until now, most HOR studies just focused on atomic systems 6,9,11,[15][16][17]19,21 or simple molecules such as H 2 + 18,20 and usually relied on the strong-field approximation. 6,9,15,21 The pulses commonly used in the literature are also quite long, of five cycles or longer 9,18,19,21 (except for the work 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Treating many electrons will add further complexities where adequacy of the mean-field orbital picture is not obvious. Consequently, computational studies of electron dynamics under strong field on realistic molecular models are rather scarce (although the reference list herein [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] is not exhaustive). The size of the molecules that have been treated so far is also limited.…”
Section: Introductionmentioning
confidence: 99%